The role of halal awareness and halal certification in influencing non-muslims’ purchase intention. - Abdul Aziz, Yuhanis; Chok, Nyen Vui (2012)
The aim of this study is to determine the relationships between halal awareness, halal certification, food quality, marketing promotion and brand with intention to purchase halal products among the non-muslim community in Malaysia. The data was collected through a self-administrated questionnaire survey that was distributed using convenience sampling. The sample consisted of 226 non-muslim consumers. Structural equation analyses indicated halal awareness, halal certification, marketing promotion and brand were positively related to purchase intention, whereas food quality was negatively associated with it. The findings clearly indicate that even though halal certification is an option for food manufacturer; they should consider applying for certification if they aim to capture the market globally. It is critical for food manufacturers to maintain the reputation of their product brand and do intensive promotion because these marketing-related factors are important predictors to halal purchase intention. Theoretically, the current study is one of the first attempts to develop and empirically test a conceptual model on halal purchase intention by integrating halal components with marketing related components.